An officer as a subject of professional socialization of army conscripts - Roman Nikolaevich Kalambet; Aminet Maghametovna Siyukhova (Вестник Майкопского государственного технологического университета, 2023)
The article analyzes the socializing effect of social institutions on the formation of an officer’s professional identity as the main subject of socialization of army conscripts. The officer appears to be the main element of the army as a social institution, and the central link in the communication system that transmits information flows from the high command to the direct executors of orders and commands, and vice versa. It is indicated that at the beginning of the service the officer should have a wide range of personal qualities, among which must necessarily be developed morality, rational self-criticism and a constant need for self-improvement, a conscientious attitude to his professional duties, a humane attitude to his subordinates, mental stability and prevalence of optimistic moods, good health, ability to understand people, knowledge and ability to apply ways of influencing people, desire for esthetics in an appearance and spatial environment in which the service takes place, etc. The research examines the socializing effect of the state on the officer as the main subject of the formation of an ideological component of the officer’s identity and the main guarantor of social protection of a military man. Social, economic, cultural and psychological aspects of the influence of family, school, military university and professional communication with colleagues at the place of service on the officer’s formation have been also identified. The research methodology is based on structural and functional analysis of the sphere of socializing impact on personal and professional formation of an officer. In conclusion, the idea is drawn that the effectiveness of the army in ensuring state security depends directly on the ability of officers to accumulate cultural capital.